The strategic dimension of managing human competencies in improving the competitive performance of the SAIDAL complex - krobba, Maamar; Benammour, Samir (Dirassat Journal Economic Issue, 2017)
In recent years the world has witnessed a number of key variables that have affected all institutions of varying degrees in progress and growth, and has interacted with many factors and causes in creating this change comes in the vanguard of scientific development and technical factors, and the intensification of competition in the market between the Movement of institutions, which forces them to seek ways to survive and to continue to seek the most important skills of human resources, using in different ways the leadership created and brought to the institution and further development and developed through training, motivation and performance evaluation